Embryonic Stem Cell-Derived Neurons Grown on Multi-Electrode Arrays as a Novel In vitro Bioassay for the Detection of Clostridium botulinum Neurotoxins - Jenkinson, Stephen P.; Grandgirard, Denis; Heidemann, Martina; Tscherter, Anne; Avondet, Marc-André; Leib, Stephen L. (Frontiers in Pharmacology, 2017)
Clostridium botulinum neurotoxins (BoNTs) are the most poisonous naturally occurring protein toxins known to mankind and are the causative agents of the severe and potentially life-threatening disease botulism. They are also known for their application as cosmetics and as unique bio-pharmaceuticals to treat an increasing number of neurological and non-neurological disorders. Currently, the potency of biologically active BoNT for therapeutic use is mainly monitored by the murine LD50-assay, an ethically disputable test causing suffering and death of a considerable number of mice. The aim of this study was to establish an in-vitro assay as an alternative to the widely used in-vivo mouse bioassay. We report a novel BoNT detection assay using mouse embryonic stem cell-derived neurons (mESN) cultured on multi-electrode arrays. After 21 days in culture, the mESN formed a neuronal network showing spontaneous bursting activity based on functional synapses and express the necessary target proteins for BoNTs. Treating cultures for 6 h with 16.6 pM of BoNT serotype A and incubation with 1.66 pM BoNT/A or 33 Units/ml of Botox® for 24 h lead to a significant reduction of both spontaneous network bursts and average spike rate. This data suggests that mESN cultured on multi-electrode arrays pose a novel, biologically relevant model that can be used to detect and quantify functional BoNT effects, thus accelerating BoNT research while decreasing animal use.